Pharmacological evaluation of processed Cannabis leaves as a non sedative analgesic: The novel approach - Swagata Dilip Tavhare; Mukesh B Nariya; Rabinarayan Acharya (Wolters Kluwer Medknow Publications, 2021)
Background: Ayurvedic pharmacopoeia records vivid indications of Cannabis (Bhanga) including its analgesic, sedative and intoxicant actions. For inhibition of intoxication, Ayurveda recommends certain processing (Shodhana) techniques for Cannabis. The present study is planned to evaluate the analgesic potential and sedative effects of water washed (Jalaprakshalana)-processed Cannabis sativa leaves through pharmacological experimentation. Methods: Wistar strain albino rats weighing 200 ± 20 g and Swiss albino mice (25-35 g) of either sex were used in the study. Pharmacologically validated models were used to evaluate the analgesic effects (by formalin test and tail flick method) and neuromuscular coordination by rotarod experiment. water-washed-processed Cannabis leaves powder (test drug [TD]) was administered at dose of 22.5 and 45 mg/kg for rat and mouse, respectively, against reference standard morphine sulfate (MS) 5 mg/kg and the results were evaluated statistically. Results: TD at 22.5 and 45 mg/kg showed significant decrease in paw licking response at early phase in formalin test. TD at 22.5 mg/kg showed significant increase in tail flick latency after 3 h, and in 45 mg/kg dose, it was significant up to 4 h. In rotarod experiment, TD did not show any decrease in latency of fall-off time after 1 and 3 h. Conclusion: Water-washed processed Cannabis leaves powder possesses significant analgesic effect at 22.5 mg/kg (250 mg human dose) and 45 mg/kg (500 mg human dose) comparable to MS 5 mg while nonsignificant effect in neuromuscular in-coordination, thus devoid of sedative effect.